Особливості тунелювання у багатошарових наноструктурах - Чернишов, М. О.; Сукач, С. О.; Пащенко, О. Г. (ХНУРЕ, 2019)
Multilayer nanostructures are increasingly used in various fields of science and technology. This is due, first of all, to the detection of specific electrical, magnetic, mechanical, thermal and optical properties of nanolamines. Purpose: to conduct analytical review and analysis of multilayer nanostructures, their types and properties and features of tunneling in them.In this paper, the physical and chemical properties of multilayered nanomaterials, as well as the tunneling process and its features are considered.The analytical review shows the relevance of the development of this direction and points to the promising use of multilayer nanostructures in electronics.
Keywords: Особливості тунелювання у багатошарових наноструктурах